Levantamento de requisitos e desenvolvimento da plataforma digital GreenFoods - Cruz Junior, Aparecido Souza da (2023)
According to data, about 30% of food produced in the country is wasted, equivalent to about 46 million tons of food per year. These foods should both reach a needy part of the population and represent invested capital that is lost. Several projects tackle the first from this point of view, but there is a need to tackle this problem from the other point of view; i.e., that wasted food is lost invested capital and that recovering part of this value can at the same time provide an attractive service to a portion of the middle class. In this sense, this work aims to develop an MVP on the Marketplace platform that enables the sale of food that would otherwise be wasted. The project will be a Web tool based on the Django framework native to the Python language with a Sqlite database. For the layout of the pages, Bootstrap and JavaScript technology will be used. Through the platform, it will be possible to sell products marketed by restaurants, which instead of being discarded can be sold at an affordable price, thus avoiding the waste of these foods and at the same time recovering the capital invested in these perishable products.